2018
DOI: 10.1177/0284185118802598
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion imaging in monitoring the function of kidney allograft

Abstract: Background Non-invasive alternatives to percutaneous renal biopsy are sought for follow-up of renal allografts. Purpose To evaluate the feasibility of intravoxel incoherent motion (IVIM) imaging in monitoring and predicting the function of renal allografts. Material and Methods Thirty-five kidney recipients were examined on a 1.5-T MR unit approximately three and 18 months after transplantation. Based on estimated glomerular filtration rate (eGFR), patients were divided into three groups: improved; decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…First, ADCD as a marker of perfusion-free diffusion decreased in patients maintained on CsA whereas it increased in patients converted to everolimus. The ADCD has previously been shown to be reduced in various states of acute and chronic kidney diseases and to correlate to biological kidney function markers and interstitial fibrosis [9,18,[22][23][24][25]. This course parallels the improvement of eGFR in EVE-treated patients reported in the ZEUS trial, which was by trend also observed in our sub-study population.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…First, ADCD as a marker of perfusion-free diffusion decreased in patients maintained on CsA whereas it increased in patients converted to everolimus. The ADCD has previously been shown to be reduced in various states of acute and chronic kidney diseases and to correlate to biological kidney function markers and interstitial fibrosis [9,18,[22][23][24][25]. This course parallels the improvement of eGFR in EVE-treated patients reported in the ZEUS trial, which was by trend also observed in our sub-study population.…”
Section: Discussionsupporting
confidence: 85%
“…The DWI-derived fraction of perfusion FP showed no significant changes over time nor between medication groups. Studies in kidney grafts have suggested lower FP values in cases of decreased graft function and acute rejection as well as to correlate to chronic tubulo-interstitial damage [18,24,27]. In our study, the number of cases might have prevented a significant finding.…”
Section: Discussionmentioning
confidence: 58%
“…Renal cysts and areas of parenchymal scarring were excluded form ROIs. The values of signal intensities from ROIs were averaged and incorporated into the locally developed script written in Matlab (R2014b, Mathworks, Natick, USA) and fitted in 2 ways [20]: 1) ADC was calculated using a standard mono-exponential model expressed by equation:…”
Section: Ivim Calculationsmentioning
confidence: 99%
“…27 Findings-Similar to ADC, IVIM imaging detected decreased diffusion as well as lower perfusion in native kidney diseases [48][49][50][51][52][53][54][55] and dysfunctional renal allografts. [56][57][58] However, by yielding a larger number of renal physiological parameters, IVIM imaging offers new insights into renal pathophysiology. Studies demonstrated IVIM-measured diffusion coefficients had higher accuracy compared with ADC in discriminating renal lesions and that f p could provide information regarding lesion vascularity, 59,60 although others suggested that IVIM could not provide more information in the evaluation of renal dysfunction.…”
Section: Intravoxel Incoherent Motion Imagingmentioning
confidence: 99%